2018
DOI: 10.3390/bioengineering5020045
|View full text |Cite
|
Sign up to set email alerts
|

3D Cell Migration Studies for Chemotaxis on Microfluidic-Based Chips: A Comparison between Cardiac and Dermal Fibroblasts

Abstract: Fibroblast migration to damaged zones in different tissues is crucial to regenerate and recuperate their functional activity. However, fibroblast migration patterns have hardly been studied in disease terms. Here, we study this fundamental process in dermal and cardiac fibroblasts by means of microfluidic-based experiments, which simulate a three-dimensional matrix in which fibroblasts are found in physiological conditions. Cardiac fibroblasts show a higher mean and effective speed, as well as greater contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Little is known about the difference between cardiac fibroblasts and dermal fibroblasts. Pérez-Rodríguez et al observed that their cell migration abilities in response to cytokines are distinct [29]. Although several reports have demonstrated that trans-differentiation and MMP1 expression in dermal fibroblasts is associated with dermal wound healing and fibrosis, we revealed that the response of these cells to DOX is less than that of CFs.…”
Section: Discussioncontrasting
confidence: 53%
“…Little is known about the difference between cardiac fibroblasts and dermal fibroblasts. Pérez-Rodríguez et al observed that their cell migration abilities in response to cytokines are distinct [29]. Although several reports have demonstrated that trans-differentiation and MMP1 expression in dermal fibroblasts is associated with dermal wound healing and fibrosis, we revealed that the response of these cells to DOX is less than that of CFs.…”
Section: Discussioncontrasting
confidence: 53%
“…Collagen gels of 2.5 mg/ml concentration and pH 7.4 were created by mixing collagen type I (BD Bioscience), NaOH, Dulbecco's phosphate buffered saline, DPBS (Thermo Fisher), and culture medium with suspended cells (after trypsinization and centrifugation). MCF-7 and MDA-MB-231 cells were mixed with gel solutions at a final concentration of 2×10 5 cells/ml and pipetted into the gel cavities of the microdevice, as in previous reports [20], [42]- [46].…”
Section: Cell Migration Within 3d Extracellular Matrixmentioning
confidence: 99%
“…Under normal conditions, fibroblasts migrate at a speed of ∼10 µm/h, but this can vary significantly in the presence of growth factors and cytokines (Ware et al, 1998;Pérez-Rodríguez et al, 2018). As noted above, individual grid spaces are 10 × 10 µm, so the baseline migration speed was set at 1 grid space per hour.…”
Section: Fibroblast Migration Speed and Density Affect Collagen Spatimentioning
confidence: 99%